Cellulose from lignocellulosic waste - Michelin, Michele (2015)
Bioconversion of renewable lignocellulosic biomass to biofuel and value-added products is globally gaining significant importance. Lignocellulosic wastes are the most promising feedstock considering its great availability and low cost. Biomass conversion process involves mainly two steps: hydrolysis of cellulose in the lignocellulosic biomass to produce reducing sugars and fermentation of the sugars to ethanol and other bioproducts. However, sugars necessary for fermentation are trapped inside the recalcitrant structure of the lignocellulose. Hence, pretreatment of lignocellulosic wastes is always necessary to alter and/or remove the surrounding matrix of lignin and hemicellulose in order to improve the hydrolysis of cellulose. These pretreatments cause physical and/or chemical changes in the plant biomass in order to achieve this result. Each pretreatment has a specific effect on the cellulose, hemicellulose, and lignin fraction. Thus, the pretreatment methods and conditions should be chosen according to the process configuration selected for the subsequent hydrolysis steps. In general, pretreatment methods can be classified into four categories, including physical, physicochemical, chemical, and biological pretreatment. This chapter addresses different pretreatment technologies envisaging enzymatic hydrolysis and microbial fermentation for cellulosic ethanol production and other bioproducts. It primarily covers the structure of lignocellulosic wastes; the characteristics of different pretreatment methods; enzymatic hydrolysis; fermentation and bioproducts; and future research challenges and trends.